Stress and Coping Strategies among Pregnant Women attending Antenatal Clinic of a Teaching Hospital in eastern Nepal - Tripathi, Pratikshya; Devkota, Ganesh (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aim: To find out the stress and coping strategies among pregnant women attending antenatal clinic. Methods: A descriptive, cross-sectional research design was used for the study. The sample was taken from an antenatal outpatient department of Nobel Medical College Teaching Hospital. A total of 300 pregnant women was selected by using non- probability consecutive sampling technique. Data was collected by using standard tool, Pregnancy Stress Rating Scale (PSRS) and Brief Cope. Data analysis was done by descriptive and inferential statistics. Results: The study revealed that 40.7% of the respondents experienced a high level of stress and 84.0% of respondents had used adequate coping strategies where “self- distraction” was the most used coping strategy by the respondents with a mean score (2.99±.56). Stress and coping strategies had positive mild correlation (r=0.040). Conclusions: More than one-third of the respondents had experienced a high -level stress and the majority of the respondents had used adaptive coping strategies. The different methods of coping strategies during pregnancy should be expanded as per the best available evidence to lower stress and other adverse outcomes of stress. Keywords: Brief cope, coping strategies, pregnancy stress rating scale, stress